Detecção de Chlamydia Trachomatis por PCR em tempo real em uma amostra da população feminina de Maceió atendida em serviços de saúde privados e públicos - Lobo, Carlos Daniel Passos (2011)
Sexually transmitted infections are relatively frequent and constitute a serious public health problem in almost everyone. Chlamydia trachomatis is the organism responsible for more than half the cases of nongonococcal urethritis, as well as numerous cases of cervicitis. Their behavior is characterized mostly by the absence of symptoms, is of great concern, especially for sequels that can cause, such as infertility in women. In most developing countries there are no data on incidence or prevalence of Chlamydia trachomatis national character. Therefore, usually, work with national estimates from other countries and regions worldwide, provided mainly by the World Health Organization. For lack of more precise information mainly from Brazil and the State of Alagoas, this study aimed to verify the actual incidence of Chlamydia trachomatis infection in Maceió, and relate to the clinical, cytological and colposcopic so that you demonstrated the importance of their screening, encouraging this approach in favor of women's health. Methodology was used as the detection of chlamydia by real-time PCR in 514 samples and sensitivity and specificity were increased, providing meaningful data. The results showed that women between 20 and 35 years have a higher prevalence of chlamydial infection, with a prevalence in the study period of 4.08%. We also observed that there is no relationship between clinical and vaginal discharge and burning with the obligatory presence of chlamydia was only significant, the results of colposcopy, wich in most cases they were changed was PCR positive. The number of positive results on samples collected in the public service is far superior to the particular service. The prevalence results leads us to conclude that there is a relationship between socioeconomic status and chlamydia infection, since the women of the city of Maceió trated at medical services salgadinho not have financial conditions to be met in private clinics.